Algunas fuentes históricas de la política exterior de Chile - Alamos Varas, Pilar (Estudios Internacionales, 1999)
This paper seeks to determine the aspects of permanence and change in Chile’s foreign policy from a historical perspective, relating the periods of stability with continuity and that of internal changes with innovative visions. In this way, behavioral guidelines are identified aimed at projecting them from a historical perspective and adapting foreign policy instruments to new circumstances. In this way, it is highlighted that principles such as the legalistic tradition, the doctrine of the balance of power, the ambiguous relationship with the United States and the importance assigned to the Pacific Ocean, are a constitutive part of the country’s diplomatic tradition, which have been present since the origins of the republic.